1988
DOI: 10.1007/bf00025103
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of in vitro regeneration in alfalfa (Medicago sativa L.)

Abstract: The genetic control of plant regeneration from callus culture was studied in tetraploid alfalfa (Medicago sativa L .) . Seven cultivars (total 72 plants) were screened for regenerability . Ladak had the best regeneration response, in which 42% of the plants regenerated . Four regenerable plants and three nonregenerable plants were used to form 10 F, hybrids and three S, populations . Segregation ratios in the populations suggested that regenerability of alfalfa via petiole culture was under the control of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 17 publications
2
20
0
1
Order By: Relevance
“…The other medium (PM) formulation had been optimized for somatic embryogenesis from Cl 830 immature cotyledons (Loiseau, 1996) Shoot apices of P axiphium and immature cotyledons of P elatius were particularly responsive to the modification of the medium. Such genotype x culture medium interactions were previously described in alfalfa (Wan et al, 1988) and soybean (Komatsuda et al, 1991). Some nonembryogenic genotypes on the non-optimized medium have produced few somatic embryos on the optimized medium.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The other medium (PM) formulation had been optimized for somatic embryogenesis from Cl 830 immature cotyledons (Loiseau, 1996) Shoot apices of P axiphium and immature cotyledons of P elatius were particularly responsive to the modification of the medium. Such genotype x culture medium interactions were previously described in alfalfa (Wan et al, 1988) and soybean (Komatsuda et al, 1991). Some nonembryogenic genotypes on the non-optimized medium have produced few somatic embryos on the optimized medium.…”
Section: Introductionmentioning
confidence: 88%
“…Moreover, within each species, a strong genotypic effect is frequently observed and, in most cases, the genetic mechanism of plant regeneration remains unknown. Some reports concerning somatic embryogenesis in Medicago sp (Wan et al, 1988) and Zea mays L (Cowen et al, 1992) suggested that few genes were involved in somatic embryogenic ability. Genotype x culture medium interactions were shown in Medicago sp (Wan et al, 1988), Glycine max L (Mer) (Komatsuda et al, 1991), Zea mays L (Duncan et al, 1985) and Oryza sativa L (Hartke and Lörz, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of genotype on in vitro growth and differentiation patterns has been reported in a number of crop plants (Henry et al, 1994). The genetic basis of in vitro response has been analyzed in several plant systems including alfalfa (Wan et al, 1988;Kielly and Bowley, 1992;Crea et al, 1995), barley (Foroughi-Wehr et al, 1982;Komatsuda et al, 1989;Özgen et al, 2005), sunflower (Encheva et al, 2004), cotton (Gawel and Robacker, 1990), maize (Nesticky et al, 1983;Tomes and Smith, 1985), petunia (Dulieu, 1991), rice (Quimio and Zapata, 1990;Abe and Futsuhara, 1991;Yan et al, 1996;Kuroda et al, 1998), rye (Rakoczy-Trojanowska andMalepszy, 1993), tomato (Frankenberger et al, 1981;Koorneef et al, 1987;Soniya et al, 2001), wheat (Lazar et al, 1984;Ou et al, 1989;De Boyser et al, 1992;Lange et al, 1995;Dornelles et al, 1997;AbdelHady, 2006;Ozbay and Özgen, 2010), eggplant (Chakravarthi et al, 2010) and pearl millet (Mythili et al, 1997). Nesticky et al (1983) noted significant reciprocal effects in the basic of combining ability and high values of reciprocal effects in corn tissue culture.…”
Section: Introductionmentioning
confidence: 99%
“…As indicated by Zhou and Konzak (1992), the percentage of green-plant regeneration from the anther culture of wheat was under the control of nuclear genes and the action of these genes was predominantly additive. Addit ive and dominant effects have also been reported for the anther culture of barley (Dunwell et al, 1987;Powell, 1987 ;Hou et al, 1994) and rice (Quimio and Zapata, 1990) and in vitro callus formation and plant regeneration in alfalfa (Wan et al, 1988) and red clover (Poerba et al, 1997). Recently, several studies on the factors influencing callus induction and plant regeneration in anther culture of sorghum have been reported (Wen et al, 1991;Kumaravadivel and Rangasamy, 1994;Nakamura et al, 1997;Can et' al., 1998).…”
mentioning
confidence: 99%